Child, school, home determinants of academic performance - Florencio, Cecilia A. (EDUKASYON)
"This study was concerned with the determinants of school-related behavior, in particular the relationship between health and nutritional status and academic performance. Such a concern is in place whenever our educational system sets for itself the objective of reducing disparities in education and raising the overall quality and efficiency of education. Although construction of new classrooms, provision of textbooks and other learning materials and training of teachers are necessary to improve the quality of education, it is illogical to expect that these will make up for the differences in learning that could arise because of biological impediments.